An Enterprise Feature Ontology for Feature‐Based Product Line Engineering. Issue 2 (21st August 2019) - Krueger, Charles; Clements, Paul
ABSTRACT: Feature‐based software and systems product line engineering (feature‐based PLE) has emerged as a modern, repeatable, codified, and proven‐in‐practice specialization of generic product line engineering (PLE) practice. Feature‐based PLE involves an automation‐supported configuration of engineering and operations artifacts from across an enterprise to reflect the feature choices a product embodies. Configuration of artifacts based on feature choices is a powerful narrative, but what actually constitutes a feature? A feature is a distinguishing characteristic that sets products apart (Kang et al. 1990), but in practice this concept encompasses a broad spectrum of granularity. Stakeholders who are concerned with the finest‐grained differences are very different from those who care about the coarsest‐grained differences. This paper presents an ontology for features that is capable of supporting an entire enterprise of product line engineering and business operations, and shows how various stakeholders throughout the enterprise can interact with these different kinds of features.